121k views
1 vote
Simplify 3-2(x+1) + (5x-4)

2 Answers

4 votes

3-2(x+1) + (5x-4)

pretend that there is a +1 in front of the second bracket

3-2(x+1) +1 (5x-4)

multiply the first bracket by -2

(-2)(x)=-2x

(-2)(1)=-2

multiply the second bracket by +1

(1)(5x)=5x

(1)(-4)=-4

3-2x-2+5x-4

-2x+5x+3-2-4 ( combine like terms)

3x+3-2-4

3x+1-4

Answer:

3x-3

User Paul Watson
by
6.0k points
1 vote

Answer:

3 (x - 1)

Explanation:

Simplify the following:

3 - 2 (x + 1) + 5 x - 4

Grouping like terms, 3 - 2 (x + 1) + 5 x - 4 = -2 (x + 1) + 5 x + (3 - 4):

-2 (x + 1) + 5 x + (3 - 4)

3 - 4 = -1:

-2 (x + 1) + 5 x + -1

-2 (x + 1) = -2 x - 2:

5 x + -2 x - 2 - 1

Grouping like terms, 5 x - 2 x - 2 - 1 = (5 x - 2 x) + (-2 - 1):

(5 x - 2 x) + (-2 - 1)

5 x - 2 x = 3 x:

3 x + (-2 - 1)

-2 - 1 = -3:

3 x + -3

Factor 3 out of 3 x - 3:

Answer: 3 (x - 1)

User Sarumont
by
5.3k points